Concept of Net Zero Energy Building in Kashmir (International Journal of Innovative Research in Engineering & Management, 2022)
Global Buildings account for up to 40%  of world energy consumption and 36% of carbon dioxide  emissions. Consumption is anticipated to increase by up to  50% by the year 2030. The construction industry in India  consumes 70% of all electricity generated in the country.  According to studies, buildings utilize more than half of  their energy for tenant comfort, such as cooling and  lighting. Building energy consumption will continue to rise  unless buildings can be built to create enough energy to  meet the growing energy demand of these structures. A zero-energy building has zero net energy consumption,  which indicates that the entire quantity of energy required  by the structure over the course of a year is equal to the  amount of energy produced on or off the site. These  structures produce fewer greenhouse gases and have a  lower impact on the environment. This research aims to  review some material on zero-energy buildings in India  and recommend solutions for tenants to reduce their energy  consumption. A building with zero net energy usage is referred to as a  zero-energy building (ZEB). In recent years, ZEBs have  gotten a lot of attention in a lot of nations because they are  seen as a key technique for achieving energy conservation  and lowering greenhouse gas emissions. The concept of  going to ZEB via law has sparked a lot of controversy in  various nations about whether it is currently feasible. With  special reference to Kashmir, the fundamental difficulties  for establishing ZEB are examined from both an  engineering and an architectural standpoint. Also being  considered are the necessary arrangements that must be  deployed in Net Zero Energy Buildings in the Kashmir  division of the UT of Jammu & Kashmir, India, as well as  other crucial issues.
Keywords: Energy; Kashmir; Solar Heater; Solar PV; Trombe Wall; Zero Energy